2015
DOI: 10.1142/s021798491550102x
|View full text |Cite
|
Sign up to set email alerts
|

The generation of accelerated electrons in the nanosecond discharge in the short interelectrode gap

Abstract: Electrical, optical and polarization characteristics of nanosecond discharges in the short interelectrode gap have been experimentally researched. The conditions and mechanisms of accelerated electrons formation are established. The estimates of energy, the length of accelerated electrons run and electron beam generation efficiency in the investigated discharge are obtained. The formation of electron beams is confirmed by the studies of polarization of spontaneous discharge irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A general block diagram of the experimental setup is shown in figure 2. (A detailed description of experimental setup and the registration systems for the discharge electrical and optical characteristics is given in [8]. )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A general block diagram of the experimental setup is shown in figure 2. (A detailed description of experimental setup and the registration systems for the discharge electrical and optical characteristics is given in [8]. )…”
Section: Methodsmentioning
confidence: 99%
“…The breakdown of a high-voltage pulsed discharge in inert gas is, under some conditions, accompanied by formation of high-energy electron beams in the discharge space. In recent years electron beams have been found experimentally in nanosecond electrical discharges in inert gases at pressures up to 1 atm [1][2][3][4][5][6][7][8]. For practical applications, non-equilibrium and non-stationary low-temperature plasmas with a large area ('plasma sheet') are of great interest and are widely used in various technological processes (plasma and ion beam etching, plasma-chemical deposition) and as sources of pulsed optical radiation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Back in the last century, it was shown that this type of discharge develops with the participation of X‐rays and runaway electrons which arise early in the discharge and provide gas preionisation [4–6]. In recent years, interest in the phenomenon of runaway electrons has greatly increased, see collection book [3], reviews [7, 8], and papers [9–30]. There are four main groups of discharges in gases, with exception of those used in plants for controlled thermonuclear fusion, in which runaway electrons and/or X‐rays were registered.…”
Section: Introductionmentioning
confidence: 99%
“…By now, many research papers have reported on the generation of X-rays and runaway electron (RAE) beams during the nanosecond breakdown in high-pressure gases, including atmospheric-pressure air, at the voltage pulse amplitude of ∼100 kV and higher (see, e.g. related studies [1][2][3][4][5][6][7][8][9][10], reviews [11,12], and monographs [13,14]). The study of this phenomenon allowed us to understand what basic requirements should be met for detection with collectors of runaway electron beams in gas diodes and gave us the idea of how the amplitude and duration of the beam's current pulse are influenced by the gas kind and pressure as well as by the rise time and the amplitude of the voltage pulse.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the amplitude of a runway electron beam current realised in SF 6 with a tubular cathode of 6 mm in diameter at the voltage rise time of ∼2 ns increased considerably as the gap width was decreased from 12 to 8 mm [32]. Reasoning that the beam amplitude is determined by the voltage across the gap, all other things being equal, at the instant of generation of runaway electrons [1–27], it can be assumed that a decrease in the electrode spacing increased the gap voltage [32]. The assumption is indirectly supported by research data on a runaway electron beam produced in nitrogen with the gap of 12 mm and tubular cathode with the diameter of 6 mm at the voltage rise time of 0.3 ns [33], showing a considerable increase in the voltage across the gap and the beam current amplitude with a decrease in the pressure.…”
Section: Introductionmentioning
confidence: 99%